2016
DOI: 10.1098/rstb.2015.0146
|View full text |Cite
|
Sign up to set email alerts
|

Developmental influences on fertility decisions by women: an evolutionary perspective

Abstract: Developmental environments are crucial for shaping our life course. Elements of the early social and biological environments have been consistently associated with reproduction in humans. To date, a strong focus has been on the relationship between early stress, earlier menarche and first child birth in women. These associations, found predominately in high-income countries, have been usefully interpreted within life-history theory frameworks. Fertility, on the other hand—a missing link between an individual's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 149 publications
0
31
0
Order By: Relevance
“…, [8,9 •• ]). Psychosocial acceleration theory emphasizes that parenting and household contexts provide important cues to the child about levels of extrinsic morbidity-mortality in the larger ecology.…”
Section: Psychosocial Acceleration Theory: a Primermentioning
confidence: 99%
See 1 more Smart Citation
“…, [8,9 •• ]). Psychosocial acceleration theory emphasizes that parenting and household contexts provide important cues to the child about levels of extrinsic morbidity-mortality in the larger ecology.…”
Section: Psychosocial Acceleration Theory: a Primermentioning
confidence: 99%
“…Stress response systems further coordinate across other physiological systems ( e.g. , the gonadal axis) to regulate sexual maturation and reproduction [9 •• ,19,2527]. …”
Section: Psychosocial Acceleration Theory: a Primermentioning
confidence: 99%
“…Ancestral environments determine the speciesspecific position on the life-history continuum. Prenatal, childhood, immediate and predicted environments then finetune an individual's position on the continuum relative to peers [23]. In other words, life-history strategies are facultative-determined by our childhood environments toward relatively fast or slow trajectories, but likely to remain pliable in the face of new information.…”
Section: (B) Life-history Theorymentioning
confidence: 99%
“…Coordinating the development of a broad cluster of life historyrelevant traits may depend on consistent environmental information and using childhood environmental conditions to predict adult environmental conditions may only create optimal strategies if the two environments are similar (Alvergne et al 2008; Cabeza de Baca and Ellis 2017; Nettle et al 2011). Whilst other studies have shown that women who experienced childhood stress are more likely to experience adult stress (Coall et al 2016), correlations between our childhood and adulthood environment measures were weak at best (Table S7). Although they captured different environmental levels (family versus neighbourhood conditions), this could suggest that adverse childhood conditions are not necessarily associated with adverse adult conditions, and therefore a reliance on childhood information may result in behaviour less well-suited to adult conditions (i.e.…”
Section: The Importance Of Socioeconomic Disadvantage and Environmentmentioning
confidence: 91%
“…Some life history events such as menarche and age at first birth will predate contemporary socioeconomic/environmental conditions (Amir et al 2016;Ellis 2004), but others occurring later on in the trajectory, such as parental investment, are plausibly still affected by contemporary environmental exposure (Coall et al 2016;Kaplan and Lancaster 2003) and there may be some elements of life history strategy that respond to new environmental information throughout the lifespan (Kubinski et al 2017). Early life environmental conditions are nevertheless thought to be particularly important for calibrating life history strategies as harshness in childhood may directly impair somatic state or serve as a cue for later environmental conditions (Rickard et al 2014).…”
Section: The Importance Of Socioeconomic Disadvantage and Environmentmentioning
confidence: 99%